Preparation, Quality Control and Stability Studies of Avipattikar churna - Patil, Sonali; Shah, Shruti (Journal of Drug Delivery and Therapeutics, 2019)
Throughout world more people are turning to use medicinal plant products in healthcare system. Worldwide need of alternative medicine has resulted in growth of natural product markets and interest in traditional systems of medicine. Proper integration of modern scientific techniques and traditional knowledge is important. There is a growing focus on the importance of traditional health care system (viz. Ayurveda, Unani, Homoeopathy, Yoga) in solving health care problems. Systematic approach and well-designed methodologies for the standardization of herbal formulations are developed. In the present study preparation of Avipattikar Churna was carried out and then it was subjected to various quality control parameters. The formulation was prepared as per the guidelines mentioned in pharmacopeia & various tests performed were physical properties (such as moisture content) , biochemical test, ash value, HPLC, IR spectroscopy. The above parameters can be used as preliminary standardization for quality control of Avipattikar Churna . Keywords: Standardization, herbal formulation, Avipattikar Churna, Physicochemical properties.